Enhance librarians’ competency as Google experts: experience in Universiti Sains Malaysia (Meningkat kompetensi Pustakawan sebagai pakar rujuk aplikasi Google : pengalaman di Universiti Sains Malaysia) - Ahmat, Muhammad Akmal (2016)
We often heard about Neil Gaiman's quote, a renowned novelist who mentions "Google can bring you back 100,000 answers. A librarian can bring you back to the right one ". Based on this quote, the majority of the librarian making it as the doctrine to prove how important librarianship to the community. Various interpretation keep appear to describe the purpose of the quote. Nevertheless, it remains a question whether the librarian himself/herself have taken an action to increase the knowledge in becoming the experts of Google applications or else. What is the form of benefits that can be gained by becoming Google application experts? Especially, how the Librarian of Universiti Sains Malaysia improve competency to be expert on Google applications?